The Role of Waqf and Overcoming the Economy due to the Covid-19 Pandemic Social in Indonesia - Nawawi Nawawi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The research has found that one of the principles of waqf in Indonesia is to hold back the capital and give the results to people in need. Consequently, waqf has productive potential that needs to be developed dynamically. This is where the development of waqf financial technology is needed to facilitate the liquidity of online market players according to Sharia by bringing together demand and supply during the lockdown due to the pandemic. In Islamic law, saving Micro, small and Medium enterprises (MSMEs) that are threatened with bankruptcy due to the Covid-19 pandemic can be categorized as waqf recipients (mauquf 'alaih). The Indonesia government can optimize waqf both cash waqf schemes, productive and waqf linked sukut (record) to build waqf-based infrastructure such as Waqf Hospital (WH) specifically for Covid-19 victims, waqf Personal Protective Equipment (PPE), waqf masks, waqf polyclinics, Waqf Isolation Houses (WIH), procurement of waqf ventilators, waqf universities and others.